Mental Health Research in Correctional Settings: Perceptions of Risk and Vulnerabilities - Johnson, Mark E. (Ethics Behav, 2015)
With over half of individuals incarcerated having serious mental health concerns, correctional settings offer excellent opportunities for epidemiological, prevention, and intervention research. However, due to unique ethical and structural challenges, these settings create risks and vulnerabilities for participants not typically encountered in research populations. We surveyed 1,224 researchers, IRB members, and IRB prisoner representatives to assess their perceptions of risks associated with mental health research conducted in correctional settings. Highest-ranked risks were related to privacy, stigma, and confidentiality; lowest-ranked risks were related to prisoners’ loss of privileges or becoming targets of violence due to having participated in research. Cognitive impairment, mental illness, lack of autonomy, and limited access to services emerged as the greatest sources of vulnerability; being male, being female, being over age of 60, being a minority, and being pregnant were the lowest-ranked sources of vulnerability. Researchers with corrections experience perceived lower risks and vulnerabilities than all other groups, raising the question whether these researchers accurately appraise risk and vulnerability based on experience, or if their lower risk and vulnerability perceptions reflect potential bias due to their vested interests. By identifying areas of particular risk and vulnerability, this study provides important information for researchers and research reviewers alike.